2007
DOI: 10.1111/j.1365-2516.2007.01613.x
|View full text |Cite
|
Sign up to set email alerts
|

Posturographic analysis of balance control in patients with haemophilic arthropathy

Abstract: Musculoskeletal disorders in haemophiliacs represent the highest percentage of lesions, giving rise to haemophilic arthropathy (HA) which predominantly affects lower limbs, influencing postural control, standing and walking. Leading a sedentary lifestyle seems to influence strength and muscular resistance in haemophiliacs which, in turn, are related to articular stability and the prevention of articular degenerative processes. The objective of this work was to study alterations in balance to subsequently evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
86
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(96 citation statements)
references
References 28 publications
7
86
1
2
Order By: Relevance
“…Actualmente podemos decir que, en general, la condición física del paciente hemofílico adulto es baja, ya que hay estudios que muestran valores inferiores de resistencia aeróbica 49 , fuerza 37,50,51 , propiocepción y equilibrio 50,52,53 , respecto a los encontrados en sus pares sanos.…”
Section: La Condición Física Del Paciente Hemofílicounclassified
“…Actualmente podemos decir que, en general, la condición física del paciente hemofílico adulto es baja, ya que hay estudios que muestran valores inferiores de resistencia aeróbica 49 , fuerza 37,50,51 , propiocepción y equilibrio 50,52,53 , respecto a los encontrados en sus pares sanos.…”
Section: La Condición Física Del Paciente Hemofílicounclassified
“…Measurement of postural sway, the horizontal movement of the body around the centre of gravity, is commonly used to evaluate postural stability, and disturbance of input from the sensory systems will affect postural sway [16][17][18][19][20][21]. Studies of postural sway in young adults also suggest that fatigue of the hip and ankle muscles increases postural sway [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Gallach et al [21] compared standing balance in a group of 50 adult PWH and 25 age-matched healthy non-haemophilic men and observed greater amplitude and velocity of postural sway in men with haemophilia during standing. In a study of twenty PWH aged 22-58 years, Fearn et al [22] reported that half of haemophilic men had experienced a fall within the previous 12 months.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that patients with hemophilia displayed a worse balance and proprioception compared with healthy normal subjects [10][11][12][13].Authors hypothesized that because proprioception information is transmitted from receptors found in all tissues of the synovial joint, repeated joint bleeding into the target joint could be a contributory cause of impaired proprioception in patients with hemophilia. As the muscular function comprises not only the static control of the joint and the dynamic control of movement, but also the proprioceptive input to the central nervous system (CNS) .So further possible mechanism induced proprioception deficit in hemophilic patients may be related to the intramuscular bleeding and lower muscle strength [14,15].…”
mentioning
confidence: 99%